Inteligencia emocional y autopercepción corporal en mujeres adolescentes de 12 a 15 años de dos Instituciones Educativas Pública y Privada de Tunja (2023)
The present research was aimed at describing emotional intelligence and body selfperception in adolescent women aged 12 to 15 years from a public and private institution in the city of Tunja. The type of research was quantitative with an empirical analytical approach; a sample of 85 teen women was taken, where the sample type was non-probability type intentionally; for the evaluation, the scale was used for the assessment of expression, management, and recognition of emotions (TMMS-24) and the body shape questionnaire (BSQ).